Analisis Traffic Data ESP8266 pada Perangkat Middleware - Unang Achlison; Khoirur Rozikin; Fujiama Diapoldo Silalahi; Yogiswara (STEKOM PRESS, 2022)
Almost every house already uses a Wifi network as internet access. With the help of this Wifi network, it is used as Middleware that can be controlled and monitored when outside the home. This study engineered data packet traffic using the ESP8266 wifi module on the Middleware device network to find out how fast the data packet capture time using wifi can be controlled and monitored when outside the home. Based on the analysis, the measurement results on the IoT device network to find out how fast the data time using wifi it reaches 2.95 kbps to 7.4 kbps.